معالجة الأذيات الفموية المسببة عن الأجهزة السنية باستخدام مكيفات النسج - الشعراني, إياد (Latakia University Journal -Medical Sciences Series, 2019)
تتمتع الأجهزة السنية جيدة الصنع بقيمة وقائية وعلاجية عالية،حيث تعيد شكل الجهاز الماضغ في حالات فقد الأسنان والنسج المجاورة، مما يحسن الصحة العامة للمريض، من خلال اعادة وظائف المضغ والبلع، وتأمين الناحية التجميلية واللفظية وإعادة الحالة النفسية، إلا أن استخدامها المديد قد يسبب أذيات للنسج الفموية الواقعة تحتها. تمت معالجة الأذيات الفموية الناجمة عن استخدام الأجهزة السنية المتحركة بوساطة المواد المكيفة للنسج Tissue Conditioners المستخدمة في بحثنا والتي أعطت نتائج إيجابية من حيث: زوال الأعراض الالتهابية للغشاء المخاطي الفموي. رفع فعالية المضغ باستخدام الأجهزة المبطنة بمكيفات النسج. راحة وتقبل المرضى للأجهزة أصبحت أفضل. Properly made dentures have a high preventive and therapeutic value. They conform to the shape of the masticatory apparatus where teeth and surrounding tissues are lost. They restore the functions of mastication, swallowing, speech, aesthetics, and the patient's mental health, improving the general health of the patient. However, long-term use of dentures can impair the underlying oral tissues. Denture-caused oral impairments have been treated using tissue conditioners tested in our research which led to positive results in terms of: Disappearance of inflammatory symptoms observed in the oral mucosa. Increasing the masticatory performance using dentures relined with tissue conditioners. Better patient’s acceptance and comfort with dentures.